"We Sing in Dialects Even as We Wander Far from Home": Performing the Local in Polyglot Southern China. Issue 5 (20th October 2019) - Kielman, Adam
ABSTRACT: This article investigates the intersecting aesthetic and political dimensions of the use of local dialects by an expanding cohort of musicians in southern China. Attending to processes of composition, rehearsal, performance, and listening in a polyglot cosmopolitan setting marked by uneven linguistic competencies, I suggest a framework for understanding how the sounds of language in popular music – even when minimally understood – communicate notions of place and articulate social formations. I apply this framework to an analysis of the ways the production, circulation, and consumption of this music relate to shifting conceptions of the local in contemporary China.